The yield spread and GDP growth - Time Varying Leading Properties and the Role of Monetary Policy - Jens Hogrefe (Kiel University, Department of Economics, 2007)
The yield spread is a well documented leading indicator of GDP growth. Estrella (2005) proposes a model to explain this relationship. Within the model, the leading properties of the yield spread are determined by the monetary policy. Accordingly, changes of the leading properties that have been reported in many studies should correspond to changes of the monetary policy. This paper analyzes whether and what form of time variation of the leading properties can be found in four major industrialized countries (France, Germany, the UK and the US). The results are connected with time varying behavior of the monetary policy by modeling a joint state dependency of the leading properties and the reaction parameters of the monetary policy. Time variation of the leading properties seem to exist in all countries under consideration. For the US and Germany they are best modeled as a structural break while France and the UK exhibit recurring phases. Evidence for a link between the time variations of the monetary policy and the leading properties can be found. However, a clear determination of the leading properties by the monetary policy cannot be confirmed.
Keywords: C32; E52; E37; E43; 330; leading indicator; yield spread; GDP growth; monetary policy; Markov-Switching